Meta-Analisis pengaruh faktor daya dukung etiologi sirosis terhadap keberhasilan curcumin sebagai terapi - Winnie Nirmala Santosa; Dwi Martha Nur Aditya (MEDIA ILMU KESEHATAN, 2022)
Background: Cirrhosis is a liver disease that affects 20-30% of people in Indonesia. The etiologic of cirrhosis include autoimmune, hepatitis B, portal vein thrombosis, and alcoholism. The existence of etiological factors may but has not been proven to, influence the success of curcumin therapy.Objective: This meta-analysis examines the research to show how etiological variables might affect cirrhotic patients' response to curcumin treatment.Methods: The searching terms "curcuma," "curcumin," and "cirrhosis" were used to find articles in databases. Beginning on January 1, 2020, through August 31, 2022, search data for articles was collected. The article search procedure complies with PRISMA chart requirements.Results: Overall effect size between treatment groups vs. placebo on autoimmune factor (Ai) namely P= 1.09 (95% CI= 0.44 – 2.74); hepatitis B (HpB) namely P=0.88 (95% CI= 0.25 – 3.08); portal vein thrombosis (TVP) ie P=0.65 (95% CI= 0.14 – 2.99); alcoholic (Alk) namely P = 0.28 (95% CI = 0.04 – 1.77). This demonstrates how the HpB, TVP, and Alk variables have an impact on both groups but not the Ai factor.Conclusion: The etiological variables HpB, TVP, and Alk may affect how well curcumin treatment for cirrhosis works.